ИТТЕРДІҢ КАРБАМАТТАРМЕН УЛАНУЫНЫҢ ПАТОЛОГИЯЛЫҚ МОРФОЛОГИЯСЫ - А. Мауланов; Г. Кузембекова; Д. Калкаева; Қ. Жуманов; А. Жылқайдар; Ш. Туржигитова; А. Джангабулова; Л. Бесембаева (Animal Health and Biosafety, 2026)
This article examines the pathological and morphological changes in dogs poisoned with carbamate insecticides recorded during 2020–2025 in a suburban garden area near Almaty. Carbamate compounds are widely used in agriculture; however, improper application may cause accidental poisoning of domestic and stray dogs. The aim of the study was to determine the clinical signs, pathological-anatomical findings, and histological changes associated with carbamate poisoning in dogs. The study was conducted at the Department of Pharmacology and Animal Pathology of the Kazakh National Agrarian Research University. The study material consisted of carcasses of 7 dogs that died after suspected exposure to carbamate insecticides: 2 German Shepherds aged 3 years, 3 mixed-breed dogs aged 2 years, and 2 Poodles aged 4 years. Complete pathological-anatomical necropsy was performed. Tissue samples from the lungs, heart, liver, kidneys, stomach, intestines, and brain were collected for histological examination. The samples were fixed in 10% neutral formalin and stained with hematoxylin and eosin. The results showed that before death the poisoned dogs had excessive salivation, respiratory distress, lacrimation, diarrhea, involuntary urination, muscle tremors, and convulsions. Necropsy revealed foamy fluid in the trachea and bronchi, acute venous hyperemia and pulmonary edema, catarrhal gastritis, contraction of the small intestine, and venous congestion of the liver and kidneys. Histological examination revealed dystrophy, necrobiosis, and necrosis of hepatocytes and nephrocytes, alveolar pulmonary edema, perivascular edema, and degenerative neuronal changes in the brain. The findings indicate that acute carbamate poisoning in dogs is associated with respiratory failure, cholinergic syndrome, and toxic-hypoxic damage to internal organs. Future studies should include chemical-toxicological analysis, particularly chromatographic methods, to identify the specific carbamate compound and improve diagnostic accuracy.